Glenohumeral joint kinematics measured by intracortical pins, reflective markers, and computed tomography: A novel technique to assess acromiohumeral distance. (August 2016) - Dal Maso, Fabien; Blache, Yoann; Raison, Maxime; Lundberg, Arne; Begon, Mickaël
Abstract: Combination of biplane fluoroscopy and CT-scan provides accurate 3D measurement of the acromiohumeral distance (AHD) during dynamic tasks. However, participants performed only two and six trials in previous experiments to respect the recommended radiation exposure per year. Our objective was to propose a technique to assess the AHD in 3D during dynamic tasks without this limitation. The AHD was computed from glenohumeral kinematics obtained using markers fitted to pins drilled into the scapula and the humerus combined with 3D bone geometry obtained using CT-scan. Four participants performed range-of-motion, daily-living, and sports activities. Sixty-six out of 158 trials performed by each participant were analyzed. Two participants were not considered due to experimental issues. AHD decreased with arm elevation. Overall, the smallest AHD occurred in abduction (1.1 mm (P1) and 1.2 mm (P2)). The smallest AHD were 2.4 mm (P1) and 3.1 mm (P2) during ADL. It was 2.8 mm (P1) and 1.1 mm (P2) during sports activities. The humeral head greater and lesser tuberosities came the nearest to the acromion. The proposed technique increases the number of trials acquired during one experiment compared to previous. The identification of movements maximizing AHD is possible, which may provide benefits for shoulder rehabilitation.